OPTIMALISASI SISTEM PENGELOLAAN SAMPAH DI LINGKUNGAN KAMPUS UNIVERSITAS DIPONEGORO: UPAYA MENUJU UNDIP ECO-CAMPUS - Wiharyanto, Oktiawan; Titik, Istirokhatun; Nur, Fajar S. S (TEKNIK, 2012)
Diponegoro University as a leading institution of higher education in Central Java is expected to be a pioneerand an example in terms of waste management. But in fact now has Undip not have an adequate system of wastemanagement. Current conditions almost all existing studies program has been concentrated in the campus areaTembalang still treats conventional waste by dumping it in the trash is mixed with and without prior sortingwhich will eventually increase the weight of the existing TPS and TPA. This makes the system of wastemanagement in the UNDIP really need to be evaluated and reviewed. This study dimaksudakan to optimizewaste management system with the principles of the 3R (reuse, reduce, recycle) in order to minimize the wasteproblem. Besides this optimization also as an effort to realize the vision of the university Undip asenvironmentally friendly (eco-campus) and a role model for waste management agencies and other institutions